Early cross-modal interactions and adult human visual cortical plasticity revealed by binocular rivalry - Lunghi, Claudia (Premio Tesi di Dottorato, 2014)
In this research binocular rivalry is used as a tool to investigate different aspects of visual and multisensory perception. Several experiments presented here demonstrated that touch specifically interacts with vision during binocular rivalry and that the interaction likely occurs at early stages of visual processing, probably V1 or V2. Another line of research also presented here demonstrated that human adult visual cortex retains an unexpected high degree of experience-dependent plasticity by showing that a brief period of monocular deprivation produced important perceptual consequences on the dynamics of binocular rivalry, reflecting a homeostatic plasticity. In summary, this work shows that binocular rivalry is a powerful tool to investigate different aspects of visual perception and can be used to reveal unexpected properties of early visual cortex.